Land use changes and their effect on floodplain aggradation along the Middle-Tisza River, Hungary - Kiss, Tímea; Sándor, Andrea (Acta Geographica Debrecina Landscape & Environment series, 2019)
Land-use changes and their effect on overbank sediment accumulation were investigated on the floodplain of Middle-Tisza River. Military survey maps (1783, 1860, 1883 and 1890) and aerial photos (1950, 1965, 1980 and 2000) were used to evaluate land-use changes and to calculate the vegetational roughness of the area. To determinate the rate of overbank sedimentation sediment samples were collected from a pit, the grain-size, content of organic matter, heavy metal content (Pb, Cu, Zn, Ni and Cd) and pH were measured. Until 1950 meadows and pastures were typical on the floodplain, gallery-forest was along the river, the oxbow-lake and the artificial levee. Notable landuse changes were detected in the second half of the 20th century, as the aerial photo taken in 1965 shows extensive forestry in the area. These land-use changes affected the average vegetational roughness, as it has been doubled since the disappearance of grasslands. Land-use changes highly affect the aggradation, as the increased roughness decreases the flood velocity on the floodplain, causing accelerated aggradation. Using Pb marker horizons and grain-size changes the studied sediment profile was compared to dated profiles (Braun et al. 2003), thus, the sediment accumulation rate could be determined for the periods of 1858-1965 and 1965-2005. According to our measurements the accumulation rate was doubled since 1965, very likely in connection with the doubled vegetational roughness.